PROFIL CULTURE SHOCK MAHASISWA PERANTAU LUAR PULAU JAWA UNIVERSITAS PENDIDIKAN INDONESIA - Apriadi Bahtiar; Nandang Budiman (Journal of Innovative Counseling : Theory, Practice, and Research, 2017)
This research has a background by a phenomenon of culture shock, is a lack of ability individual to adjust themselves with different circles of culture. The theory used in this research uses Ward's theory, et al. The purpose of this research is to explore a culture shock profile the settled foreigner student off West Java, Indonesian Education University in academic year 2016/2017. The quantitative approach with descriptive method is used in this research. The sample of this research is surfeited sample that make the population as a sample in this research. The result of this research that a culture shock profile the settled foreigner student off West Java, Indonesian Education University in academic year 2016/2017 is in a moderate shock category, that make individual has realize about the different between reality and hope, it marked by so many problems happen and will be developing a set of problems for themselves. The highest culture shock experienced the settled foreigner student of PPG SM3T off West Java that happened in affective dimension is higher shock category. The result of this research should be used for basic opinion in process to make a guidance and counseling program in campus. The research recommendation is to give over to Indonesian Education University, Education Psychology and Guidance Department and next research.